Molecular Parameters Governing the Elastic Properties of Brush Particle Films - Lee, Jaejun; Wang, Zongyu; Zhang, Jianan; Yan, Jiajun; Deng, Tingwei; Zhao, Yuqi; Matyjaszewski, Krzysztof; Bockstaller, Michael R (Macromolecules, 2020)
Elucidation of the mutual influence of composition and architecture of polymer canopies on the assembly and mechanical properties of brush particle-based materials holds the promise of advancing the understanding of the governing parameters controlling interactions in hybrid materials and the development of novel functional materials. In this work, the elastic properties of three series of brush particle systems were investigated, differentiated by grafting density as dense, intermediate, and sparse brush systems. Dense and intermediate systems displayed uniform microstructures; the degree of order (measured using Voronoi cell area analysis) increased with grafting density. For dense and intermediate brush particle systems, instrumented indentation analysis revealed an increase of the elastic modulus with the degree of polymerization of tethered chains, in contrast to effective medium predictions. Furthermore, the contribution of ligands to particle interactions increased with decreasing grafting density. The results indicated that the response behavior of particle brush films in tensile-type deformations depends on dispersion interactions between ligands of adjacent brush particles. The more pronounced brush interdigitation in the case of intermediate graft densities enhanced the dispersion interactions between brush particles and hence the modulus of films. A reversed trend in modulus was observed in films of sparse brush particles that also featured the formation of string-like superstructures. Here, the elastic modulus was substantially increased for low-molecular ligands and continuously decreased with increasing degree of polymerization of tethered chains along with a transition from string-like to uniform morphologies. Independent of grafting density, the elastic modulus of the pristine polymer was recovered in the limit of a high degree of polymerization of polymer ligands.